(untitled) (Research, Society and Development, 2026)
Brega music is a genre present in Pernambuco’s culture and recognized as Intangible Cultural Heritage of the city of Recife. It represents identity, expression, and resistance of popular groups that have historically been marginalized, constituting a symbol of belonging and cultural affirmation. Music, as a cultural element, permeates people’s daily lives and directly influences their occupations, functioning as a space for leisure, socialization, and bonding. This study aimed to understand, from the perspective of Occupational Therapy, the implications of the brega musical genre on the occupations of young people from Pernambuco. This is a mixed-methods and exploratory study, with data collected through an online questionnaire and analyzed using simple descriptive statistics and the Collective Subject Discourse technique. Sixty young people aged 18 to 24 participated in the study. The results showed that brega music is present in different occupations, especially in the dimensions of leisure and social participation, promoting bonds and subjective expression among participants. Despite the stigma still associated with the genre, brega emerges as a symbolic field of resistance and identity, challenging prejudice and valuing peripheral cultural productions. From the perspective of Occupational Therapy, brega is understood as being intertwined with young people’s everyday practices, strengthening community ties and experiences of well-being. It is concluded that brega goes beyond entertainment and constitutes a legitimate expression of culture, identity, and resistance, and should be recognized by Occupational Therapy as a powerful element in understanding human occupations.